1995
DOI: 10.1172/jci118339
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of inducible and endothelial nitric oxide synthase in the rat ovary. Effects of gonadotropin stimulation in vivo.

Abstract: Nitric oxide is reportedly involved in the regulation of several ovarian processes, yet the isoforms of nitric oxide synthase (NOS) expressed in the ovary are unknown. Our purpose was to identify and localize NOS isoenzymes in the rat ovary and to examine if mRNA expression of NOS isoenzymes change after gonadotropin stimulation. Using reverse transcriptase-PCR, we demonstrated that inducible (iNOS) and endothelial (eNOS), but not neuronal, NOS mRNAs are expressed in the ovary. In a gonadotropin-stimulated rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
83
5

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 33 publications
9
83
5
Order By: Relevance
“…Therefore, the main isoform increasing during ovulation would seem to be eNOS. These results agree well with previous reports that eNOS increases after hCG injection and is localized to blood vessels in hilum and stroma [1] or thecal layer and mural granulosa cells [2] . It is well known that the LH surge induces ovarian hyperemia and vasodilation [18], which may be mediated by eNOS…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, the main isoform increasing during ovulation would seem to be eNOS. These results agree well with previous reports that eNOS increases after hCG injection and is localized to blood vessels in hilum and stroma [1] or thecal layer and mural granulosa cells [2] . It is well known that the LH surge induces ovarian hyperemia and vasodilation [18], which may be mediated by eNOS…”
Section: Discussionsupporting
confidence: 93%
“…As shown in the present results with iNOS Western blot analysis, Van Voohris et al have shown that iNOS mRNA levels are highest in the unstimulated ovary and decline with follicle growth, and also that iNOS mRNA is localized to the granulosa cells of secondary follicles and small antral follicles [1]. On the other hand, Jablonka-Shariff and Olson have reported that iNOS protein increases after hCG injection and is localized to the thecal layer and stroma [2].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations